Feasibility Study of Methanesulfonic Acid (MSA), an Alternative Lixiviant to Improve Conventional Sulfuric Acid Leaching of NCM Black Mass - Jung, Hyewon; Lee, Jeseung; Song, Ganghoon; Park, Minseo; Ahn, Junmo (Resources Recycling, 2024)
Critical minerals such as nickel, cobalt and lithium, are known as materials for cathodic active materials of lithium ion batteries. The consumption of the minerals is expected to grow with increasing the demands of electric vehicles, resulting from carbon neutrality. Especially, the demand for LIB (lithium ion battery) recycling is expected to increase to meet the supply of nickel, cobalt and lithium for LIB. The recycling of EOL (end-of-life) LIB can be achieved by leaching EOL LIB using inorganic acid such as HCl, HNO3 and H2SO4, which are regarded as hazardous materials. In the present study, the potential use of MSA (Methanesulfonic acid), as an alternative lixiviant replacing sulfuric acid was investigated. In addition, leaching ehaviors of NCM black mass leaching with MSA was also investigated by studying various leaching factors such as chemical concentration, leaching time, pulp density (P/D) and temperatures. The leaching efficiency of nickel (Ni), cobalt (Co), lithium (Li), and manganese (Mn) from LIB was enhanced by increasing concentration of lixiviant and reductant, leaching time and temperature. The maximum leaching of the metals was above 99% at 80℃. In addition, MSA can replace sulfuric acid to recover Ni, Co, Li, Mn from NCM black mass. KCI Citation Count: 1